Effects of Graphene on Mechanical Properties of Geopolymer Concrete - Kian Hong, Anderson Chan (Universiti Teknologi PETRONAS, 2020)
With the development of nanotechnology, nanomaterials have been known to have the ability to improve the strength of geopolymer. Recent findings have indicated that incorporation graphene nanoplatelets (GNPs) as a nano-filler can be used as an additive to improve the mechanical properties of composites. Therefore, the effects of the addition of graphene nanoplatelets (GNPs) on the mechanical properties of a fly ash based geopolymers were investigated. Six different geopolymer mixtures were cast, cured, and tested to determine their compressive and tensile strength. Before adding the GNPs into the mixture, it was dispersed in water with ultrasonication treatment to ensure the excellent bonding effect with the mixture. With the incorporation of GNPs, the results showed better mechanical properties where the addition of 0.3% of GNPs increased the compressive strength by 18.62 % and tensile strength by 13.55 %. Hence, with the optimum addition amount of graphene, the strength of geopolymer can be increased which eventually helps to achieve the long-term durability of structures.